2019
DOI: 10.1093/cid/ciz881
|View full text |Cite
|
Sign up to set email alerts
|

Oral vs Intravenous Antibiotics for Patients With Klebsiella pneumoniae Liver Abscess: A Randomized, Controlled Noninferiority Study

Abstract: Background Klebsiella pneumoniae liver abscess (KLA) is emerging worldwide due to hypermucoviscous strains with a propensity for metastatic infection. Treatment includes drainage and prolonged intravenous antibiotics. We aimed to determine whether oral antibiotics were noninferior to continued intravenous antibiotics for KLA. Methods This noninferiority, parallel group, randomized, clinical trial recruited hospitalized adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 28 publications
0
25
1
2
Order By: Relevance
“…Liver abscess due to K. pneumoniae is a disease that has increased in prevalence in the last few decades, especially in Asia but also in the USA [ 70 ]. The clinical picture is a set of fever, chills and right upper quadrant pain, with laboratory abnormalities, including elevated white blood cell count and alkaline phosphatase [ 71 ].…”
Section: Clinical Entitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver abscess due to K. pneumoniae is a disease that has increased in prevalence in the last few decades, especially in Asia but also in the USA [ 70 ]. The clinical picture is a set of fever, chills and right upper quadrant pain, with laboratory abnormalities, including elevated white blood cell count and alkaline phosphatase [ 71 ].…”
Section: Clinical Entitiesmentioning
confidence: 99%
“…The clinical picture is a set of fever, chills and right upper quadrant pain, with laboratory abnormalities, including elevated white blood cell count and alkaline phosphatase [ 71 ]. A combination of drainage and antibiotics is the standard treatment, especially in patients with larger abscesses [ 70 ].…”
Section: Clinical Entitiesmentioning
confidence: 99%
“…Randomisierte Studien zur oralen Therapie schwerer Infektionen gibt es mittlerweile zu Knochen-und Gelenkinfektionen [23], Bakteriämien, intraabdominellen Infektionen (z. B. Leberabszess [24]) und sogar der (teilweisen oralen Behandlung der) Endokarditis [25]. Die meisten klinischen Infektiologen sind aber in Bezug auf eine orale Therapie der Endokarditis und der S.-aureus-Bakteriämie noch sehr zurückhaltend.…”
Section: Orale Antibiotikatherapienunclassified
“…The choice of antimicrobial is based on the susceptibility profile of the pathogen. In a recent open-label randomized clinical trial, oral antimicrobial therapy was found to be noninferior to intravenous therapy in the treatment of liver abscesses caused by K. pneumoniae [ 15 ]. Recurrent infection (relapse or reinfection) has been reported following treatment of K. pneumoniae liver abscess in a minority of cases, and clinicians should be aware of this possibility [ 4 , 10 , 16 ].…”
Section: Answer: Liver Abscess Caused By Hypervirulent Klebmentioning
confidence: 99%